Land Use Suitabililty Evaluation Based on Land Capability in Mojokerto Regency - Zuhri Firdaus; Soemarno Soemarno; Sudarto Sudarto (Program Pascasarjana Universitas Brawijaya, 2018)
In its development, Mojokerto Regency experienced very rapid growth. The form of development control efforts to run optimally and sustainably is measuring the carrying capacity of the land. This study aims to evaluate the suitability between land capability and actual land use and allocation of land space patterns (RTRW) of Mojokerto Regency. Land capability is obtained by spatial analysis and overlay on several criteria for land boundary factors including soil texture, effective depth, drainage, land slope, and erosion rate. The description of actual use is obtained using landsat 8 OLI images at coverage time in May 2018. The results of the study show that the ability of land in Mojokerto Regency varies from class I land to class VIII land. The actual condition of land use in Mojokerto Regency 98% or an area of 95314.33 Ha was used according to the ability of the land, and 2% or an area of 2078.67 Ha the area used was inappropriate. Whereas in the allocation of land space patterns in Mojokerto Regency, 78.85% or an area of 76798.89 Ha was allocated accordingly, and 0.90% or an area of 875.29 Ha was allocated to exceed the capacity of the land, then 19.39% or an area of 18884.18 Ha is an allocation of land in a conditional manner so treatment is needed to optimize land use. This finding can be used to control land use and rearrangement materials for the allocation of land space in Mojokerto Regency.Keywords: Land capability, Actual land use, RTRW